Crafting the self Filipino battered women's narratives of survival and recovery - Abulon, Edna Luz Raymundo
Spousal abuse is a social problem that pervades many societies worldwide. Although a lot of research has been done on this topic, little is known about the impact of spousal abuse on the battered women's self-concept. This research attempts to fill this gap in the literature. Specifically, it addresses how four interrelated components of the self-concept, namely, the perceived self, the ideal self, self-esteem, and role identities, are affected by the experience of spousal abuse. Two research hypothesesnwere advanced: first, the experience of spousal abuse has a significant impact on the battered women's self-concept, and second, the current self-concept of battered women who are still in the cycle of abuse differs from the self-concept of battered women who have already left the cycle of abuse. Two groups of Filipino women were enlisted to participate in this qualitative study - five women who are still in the cycle of abuse (WSCA) and five women who have left the cycle of abuse (WLCA). In-depth interviews generated rich narratives which were later subjected to narrative analysis. Results confirmed both research hypotheses. Among the four components of the self-concept, the self-esteem and the role identities received the most negative impact from repeated battering episodes. On the other hand, a silencing effect happened to the ideal self component. Experiencing various forms os spousal abuse stopped the women from dreaming and planning for their future. Their high level of resiliency became their way of coping to survive the impact of the cyclical nature of domestic violence. Moreover, a comparison of the two groups' current self-concept showed that WLCA have higher levels of self-worth and self-efficacy as well as empowerment. Finally, a theoretical framework was formulated to crystallize the stages undergone by a battered woman as well as the factors that tend to affect each stage, from keeping the marriage, the various tipping points, leaving the marriage, the recovery stage, to the realization of personal strengths and eventual crafting of an empowered self.